202k views
11 votes
Umm pls help me ik how to do it but not sure on this specific one

Umm pls help me ik how to do it but not sure on this specific one-example-1
User Brann
by
5.0k points

1 Answer

9 votes

9514 1404 393

Answer:

-8, +9

Explanation:

You need factors of (6)(-12) = -72 that have a sum of +1.

From your knowledge of multiplication tables, you know that 72 = 8·9. Then -72 = (-8)(9), and those two factors have a sum of +1.

6x^2 +x -12

= 6x^2 +9x -8x -12

= 3x(2x +3) -4(2x +3)

= (3x -4)(2x +3)

User Ian Graham
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.